GenAI in the Military: Trends and Opportunities - Vasankari, Lauri; Koski, Aapo (Scandinavian Military Studies, 2026)
Generative artificial intelligence offers the potential for significant, far-reaching applications within the military domain. This article surveys current trends and explores emerging opportunities for GenAI in military operations, focusing on its integration into strategic planning, decision-making, and operational efficiency. Key areas of application include information extraction, decision support, mission simulations and information warfare. This paper further examines critical challenges such as ethical considerations, bias mitigation, hallucination management, and secure deployment within classified environments. By addressing these challenges and leveraging the opportunities presented by GenAI, military organizations can enhance their capabilities, maintain strategic advantages, and ensure preparedness for future conflicts. The paper concludes with recommendations for research, development, and collaboration across NATO and allied forces to fully harness the power of GenAI in defense and security.